Reviving African languages and culture: the case of Aleck Macheso’s aongs in Zimbabwe - Matiza, Vimbai M. (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
African countries share a common history of colonialism. Colonialism which these people went through has seen them relegating their languages and culture. It has also impacted on their development potentials. The use of colonial languages by most African countries has seen them failing to move forward using their own indigenous languages. They are either looking East or West in a bid to solve their problems. Against this background, the task of this paper is to explore and enlighten how language can be a powerful tool to liberate people and empower them towards a better future. Chacha (2003) posits that to accomplish the Pan African goals and objectives, a release, a renewal and a re – awakening for the African people is needed. Africa must embrace a new approach. The new approach rests on recognition of the role of language, an indigenous African language which will not only facilitate social integration but also spur technological and economic prosperity. It is against such an understanding that the researcher in this article wants to elaborate the importance of using indigenous languages by local people to solve their problems and be able to move on within the confines of their culture. For that noble obligation to be fulfilled, the African renaissance model will be used together with Aleck Macheso’s selected songs.